2017
DOI: 10.21037/jtd.2017.03.117
|View full text |Cite
|
Sign up to set email alerts
|

Systolic anterior motion of the mitral valve—the mechanism of postural hypotension following left intrapericardial pneumonectomy

Abstract: Systolic anterior motion (SAM) is defined as displacement of the distal portion of the anterior leaflet of the mitral valve toward the left ventricular outflow tract obstruction. SAM can occur in patients without hypertrophic cardiomyopathy (HOCM) and is a well-recognized cause for unexplained sudden hypotension in perioperative settings. We present a case of persistent orthostatic hypotension caused by SAM following left intrapericardial pneumonectomy and mediastinal lymph node dissection for squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The management of patients with SAM in RATS includes peculiar treatment strategies, which, if not promptly and properly applied, may lead to catastrophic consequences. Notably, cases of SAM-related LVOTO are already reported in noncardiac surgery [ 36 , 37 ] and thoracic surgery [ 38 ] but never in RATS. In particular, the only case report in thoracic surgery was reported by Lasala et al, which observed the development of SAM in a patient with postural hypotension 2 days after surgery in the left thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The management of patients with SAM in RATS includes peculiar treatment strategies, which, if not promptly and properly applied, may lead to catastrophic consequences. Notably, cases of SAM-related LVOTO are already reported in noncardiac surgery [ 36 , 37 ] and thoracic surgery [ 38 ] but never in RATS. In particular, the only case report in thoracic surgery was reported by Lasala et al, which observed the development of SAM in a patient with postural hypotension 2 days after surgery in the left thoracotomy.…”
Section: Discussionmentioning
confidence: 99%